IMPLEMENTASI MEDIA PEMBELAJARAN SMARTBOARD DALAM MENGEMBANGKAN LITERASI NUMERIK SISWA PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Yunita; Asep Sahrul Gunawan (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aims to describe how the use of Smart Boards is applied in mathematics learning and how the media contributes to the development of numerical literacy of elementary school students. This study uses a qualitative approach with a descriptive type. Data was collected through observation, interviews, and documentation involving classroom teachers and students as the main informants. The results show that Smart Boards help teachers convey math material in a clearer and more engaging way through visual displays, animations, and interactive activities. Students look more focused and more courageous to engage in learning activities when given the opportunity to try directly in front of the class. Teachers also feel the convenience of preparing materials because Smart Boards provide many features that support the teaching process. Despite some obstacles such as an unstable internet network and the need to adapt to new technologies, overall Smart Boards provide a more enjoyable learning experience and help improve students' numerical comprehension. These findings suggest that the use of digital media such as Smart Boards can be an effective alternative in mathematics learning in primary schools.